SISTEM DINAMIS KETERSEDIAAN BUAH PISANG DI PROVINSI BALI - Indayani, Ni Putu; Satriawan, I Ketut; Bayu Sadyasmara, Cokorda Anom (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
The demand of banana in Bali is very high and exceeds the capability of Balinese or local production and it lead to imported banana supplied from another island in Indonesia. Demand of banana will increase, especially when Hindu’s Ceremonial appearing. The aims of this research was to determine the factor that affected of banana stock, then analyze the stock of banana and compose some alternative of recommendation in order to fulfill the demand of banana in Bali. This research was conducted in Bali Province using dynamics system approach, which simulation years started on 2012 to 2021. The simulation result showed the factors that affected of banana stock in Bali was the production of banana, demand of banana and inter island supply. Further, result showed that the production of banana in Bali wasn’t able to fulfill the demand of banana in Bali. The availability of banana tends to decrease start from the beginning until the end of simulation year. Based on some of simulation scene, the effective and reasonable policy could be develop in order to fulfill the demand of banana is with land expansion from 0,4514 fraction/year to 0,5188 fraction/year, and with enhancement effort of harvest productivity from 47,67 ton/ha to 60 ton/ha. Keywords: system dynamic, availability of banana, Bali Province.